ICD 10 Classification of Non-Fatal Road Traffic Accident Cases Admitted in Tertiary Care Hospital in Central India - Yogesh Balaso Patil; Dadasaheb Dhage; Mohan Khamgaonkar (Medsci Publications, 2019)
Background: In the background of high epidemiologic propor- tions of road traffic accidents and the fact that very few explora- tory studies were reported from central India, the present study  was undertaken to study ICD 10 classification of non-fatal road traffic accident. Methodology: Total 300 road traffic accident cases admitted in ter- tiary care hospital in city during period of one year (20th may 2014 to 22nd may 2015) were included in the study with predefined in- clusion and exclusion criteria. ICD 10 coding of study subjects was recorded in the proforma. Results: Out of total 300 accident cases there were 34 (11.33%) pedal cyclist, 148 (49.33%) motorcycle occupants and 11 (3.67%) were occupants of three wheeler. Out of 83 pedestrians injured, 55 (66.26%) had collision with 2 or 3 wheeler vehicles. Out of 148 mo- torcycle occupants who were injured in accidents, 47 (31.71%) had non collision transport accidents. Out of 19 car occupants injured in accidents, 8 (42.11%) had non collision transport accidents Conclusions: Majority of pedestrians and pedal-cyclists injured had collisions with two or three wheelers. Majority of motorcycle occupants injured had non-collision transport accidents.